Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To determine if the expressions [tex]\(2(x+3)\)[/tex] and [tex]\(2x+4+2x\)[/tex] are equivalent when [tex]\(x=2\)[/tex], we need to evaluate the second expression [tex]\(2x+4+2x\)[/tex]:
1. Start with the given value of [tex]\(x = 2\)[/tex].
2. Substitute [tex]\(x = 2\)[/tex] into the second expression:
[tex]\[ 2x + 4 + 2x = 2(2) + 4 + 2(2) \][/tex]
3. Perform the multiplications first:
[tex]\[ 2(2) + 4 + 2(2) = 4 + 4 + 4 = 4 + 4 + 4 \][/tex]
4. Add the terms together:
[tex]\[ 4 + 4 + 4 = 12 \][/tex]
Now we need to compare this result to the value of the first expression [tex]\(2(x+3)\)[/tex] when [tex]\(x=2\)[/tex]:
1. Substitute [tex]\(x = 2\)[/tex] into the first expression:
[tex]\[ 2(x+3) = 2(2+3) = 2(5) = 10 \][/tex]
Because the value of the second expression is 12 and the value of the first expression is 10, the two expressions are not equivalent.
Thus, the correct option is:
- The value of the second expression is 12, so the expressions are not equivalent.
1. Start with the given value of [tex]\(x = 2\)[/tex].
2. Substitute [tex]\(x = 2\)[/tex] into the second expression:
[tex]\[ 2x + 4 + 2x = 2(2) + 4 + 2(2) \][/tex]
3. Perform the multiplications first:
[tex]\[ 2(2) + 4 + 2(2) = 4 + 4 + 4 = 4 + 4 + 4 \][/tex]
4. Add the terms together:
[tex]\[ 4 + 4 + 4 = 12 \][/tex]
Now we need to compare this result to the value of the first expression [tex]\(2(x+3)\)[/tex] when [tex]\(x=2\)[/tex]:
1. Substitute [tex]\(x = 2\)[/tex] into the first expression:
[tex]\[ 2(x+3) = 2(2+3) = 2(5) = 10 \][/tex]
Because the value of the second expression is 12 and the value of the first expression is 10, the two expressions are not equivalent.
Thus, the correct option is:
- The value of the second expression is 12, so the expressions are not equivalent.
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.